Aphantasia, dysikonesia, anauralia: call for a single term for the lack of mental imagery–Commentary on Dance et al. (2021) and Hinwar and Lambert (2021). (May 2022) - Monzel, Merlin; Mitchell, David; Macpherson, Fiona; Pearson, Joel; Zeman, Adam
Abstract: Recently, the term 'aphantasia' has become current in scientific and public discourse to denote the absence of mental imagery. However, new terms for aphantasia or its subgroups have recently been proposed, e.g., 'dysikonesia' or 'anauralia', which complicates the literature, research communication and understanding for the general public. Before further terms emerge, we advocate the consistent use of the term 'aphantasia' as it can be used flexibly and precisely, and is already widely known in the scientific community and among the general public.